Assessment of extent of skin involvement in scleroderma using shear wave elastography - Anupam Wakhlu; Abhra Chandra Chowdhury; Namita Mohindra; Saumya Ranjan Tripathy; Durga Prasanna Misra; Vikas Agarwal (Indian Journal of Rheumatology)
Introduction: Scleroderma (systemic sclerosis [SSc]) is a rare autoimmune disease which manifests as fibrosis in the skin and other internal organs. Conventionally, the modified Rodnan skin score (MRSS) has been used to quantify the extent of skin fibrosis (resulting in skin tightness) in SSc. This technique, although widely validated, is limited by the requirement of a trained, experienced assessor. Recent literature suggests that utilization of the objective ultrasound-based assessment of skin fibrosis utilizing shear wave elastography (SWE) may be a more robust technique to detect early skin tightness in SSc. Methods: We evaluated the use of SWE (assessed by an experienced radiologist) in 24 patients with SSc compared with 16 healthy controls. Results: Our patients were predominantly females, with median disease duration of 1.5 years and median MRSS of 17. There was minimal intraobserver variation in the assessment of SWE. Patients with SSc had higher SWE values (mean elasticity [Emean]) compared to healthy controls at most assessed sites for the MRSS. The Emeancorrelated significantly at all sites with the MRSS scores. At the sites where MRSS was scored as 0 (normal), the Emeanin patients with SSc was higher when compared with similarly clinical normal skin in patients with SSc, suggesting potential early involvement of these areas of the skin with fibrosis. Conclusion: SWE is a promising tool to objectively assess skin fibrosis in SSc and may be useful in detecting early, subclinical skin involvement in this disease.